COVID-19 among infants: key clinical features and remaining controversies - Nevio Cimolai (The Korean Pediatric Society, 2024)
Infants aged <1 year represent a seemingly more susceptible pediatric subset for infections. Despite this, coronavirus disease 2019 (COVID-19) infection has not been proven as more serious in this age group (outside the very early neonatal period) than in others. Indeed, a considerable number of asymptomatic infections have been recorded, and the symptoms and morbidity associated with COVID- 19 differ minimally from those of other respiratory viral infections. Whether due to an abundance of caution or truly reduced susceptibility, infections in infants have not raised the same profile as those in other age groups. In addition to direct severe acute respiratory syndrome coronavirus 2 diagnostic tests, laboratory markers that differentiate COVID-19 from other viral infections lack specificity in infants. Gastrointestinal presentations are common, and the neurological complications of infection mirror those of other respiratory viral infections. There have been relatively few reports of infant deaths. Under appropriate precautions, breastfeeding in the context of maternal infections has been associated with tangible but infrequent complications. Vaccination during pregnancy provides protection against infection in infants, at least in the early months of life. Multi-inflammatory syndrome in children and multi-inflammatory syndrome in neonates are commonly cited as variants of COVID-19; however, their clinical definitions remain controversial. Similarly, reliable definitions of long COVID in the infant group are controversial. This narrative review examines the key clinical and laboratory features of COVID-19 in infants and identifies several areas of science awaiting further clarification.